2018
DOI: 10.3389/fnmol.2018.00388
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210-5p Contributes to Cognitive Impairment in Early Vascular Dementia Rat Model Through Targeting Snap25

Abstract: Vascular dementia (VD) is the most common form of dementia in elderly people. However, little is understood about the role of microRNAs (miRNAs) involved in cognitive impairment in early VD. Here, a VD model induced by chronic cerebral ischemia and fetal bovine serum (FBS)-free cell model that detects synapse formation was established to investigate the function of miRNAs in early VD. The microarray analysis and real-time reverse transcription polymerase chain reaction (RT-PCR) showed that miR-210-5p increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 64 publications
(64 reference statements)
0
35
0
Order By: Relevance
“…Vascular dementia (VD) is the second common type of dementia (Ragusa et al, 2016;Ren et al, 2018 (Ren et al, 2018).…”
Section: Vascular Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular dementia (VD) is the second common type of dementia (Ragusa et al, 2016;Ren et al, 2018 (Ren et al, 2018).…”
Section: Vascular Dementiamentioning
confidence: 99%
“…Vascular dementia (VD) is the second common type of dementia (Ragusa et al, 2016; Ren et al, 2018). Decreased cerebral blood flow and damaged blood vessels trigger VD, initially characterized by learning and memory impairment.…”
Section: Neurological Disorders Associated With Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research investigating temporal-lobe epilepsy in rodent models has also identified differential miR-210 expression, predominantly overexpression in hippocampal regions in both chronic and acute epilepsy stages at time points ranging from 3 hours to 4 months following seizure induction (Gorter et al, 2014;Kretschmann et al, 2015;Schouten et al, 2015). Another rodent study has also highlighted that in rats subjected to 4 weeks of ischemia, modulation of the more divergent miR-210-5p guide strand affected synaptic density in the hippocampus and spatial memory performance in the Morris water maze (Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…miR-210 has two versions, miR-210-3P and miR-210-5P. miR-210-3p is the guide-strand that integrates into the RISC (RNA induced silencing complex), whereas miR-210-5p is the passenger-strand that is inactivated through degradation [19,20]. miR-210-5P is up-regulated in several malignant tumors that are associated with a variety of functionally important targets involved in cancer [21].…”
Section: Introductionmentioning
confidence: 99%